Neonatal Morbidity and Mortality of 31 Calves Derived from Somatic Cloning. (19th June 2013) - Brisville, A.‐C.; Fecteau, G.; Boysen, S.; Desrochers, A.; Dorval, P.; Buczinski, S.; Lefebvre, R.; Hélie, P.; Blondin, P.; Smith, L.C.
<x xml:space="preserve">Abstract</x> Background The neonatal period is associated with high morbidity and mortality in cloned calves. Objective To describe morbidity and mortality in cloned calves from birth to 2 years of age. Animals Thirty‐one somatic cell‐derived Holstein calves delivered at a veterinary teaching hospital. Methods Medical files were retrospectively analyzed. Results Four calves were stillborn. Five calves born alive had physical congenital defects. Twenty‐three calves had an enlarged umbilical cord. Laboratory abnormalities included acidemia, respiratory acidosis, hyperlactatemia, anemia, stress leukogram, decreased total protein, albumin and globulins, and increased creatinine. Twenty‐five calves survived the 1st hour of life. Among them, 11 stood without assistance within 6 hours of birth, 10 calves took longer than 6 hours to stand, and 4 never stood. Twenty‐two calves suffered from anorexia. Twelve calves had complications arising from umbilical cord infections. Three calves developed idiopathic hyperthermia (>40°C). Eight calves suffered from gastrointestinal problems, including ruminal distension, abomasal ulcers, neonatal enteritis, intussusception, and abomasal displacement. Mortality between birth and 3 weeks of age was 32% (10/31). Causes of death and reasons for euthanasia included stillbirths, respiratory failure, and limb deformities. Mortality between 3 weeks and 2 years of age was 19% (4/21), with deaths in this group attributed to generalized peritonitis and complications arising from umbilical infections. Overall, mortality rate within 2 years of age was 14/31 (45%). Conclusion and Clinical Importance Respiratory problems, limb deformities, and umbilical infections were the most common causes of morbidity and mortality in these cloned calves.